Lactic Acidosis in Diabetic Ketoacidosis: A Marker of Severity or Alternate Substrate for Metabolism - Bhat, Javaid Ahmad (Indian J Endocrinol Metab, 2021)
PURPOSE: The lactate level is being increasingly used as a marker of severity of illness and prognosis in multitude of critical conditions. However, its role in diabetic ketoacidosis (DKA) is not well defined. AIM: To determine the prevalence and clinical importance along with the underlying role of metformin in lactic acidosis (LA) in patients admitted with DKA. METHODS: A 2-year prospective and observational study involving 62 consenting in hospital DKA patients. Plasma lactate level on arrival, its clinical significance and relationship with morbidity and mortality in patients with DKA was evaluated. RESULTS: The prevalence of LA (lactate ≥2.5 mmol/l) among the study cohort was found to be 55% with significant LA (≥5 mmol/l) documented in 16%. The median lactate level was 2.55 mmol/l (interquartile range, 1.70–3.20). No significant difference in the severity of LA was seen with metformin use. Lactate correlated positively with initial plasma glucose (IPG) (P = 0.001) and APACHE-II Score (P = 0.002); correlated negatively with systolic blood pressure (P = 0.003), pH (P = 0.002) and severity of DKA (P = 0.001). After controlling for AKI, APACHE II score and blood pressure, lactate continued to correlate positively with IPG (P = 0.002). No mortality or significant morbidity was documented in the entire cohort. CONCLUSIONS: LA has a significant presence in patients with DKA; however, it is not associated with mortality or significant morbidity. Moreover, there was no significant difference in severity of LA with metformin use. Elevated lactate levels may be an adaptation to provide alternate substrate for metabolism in the presence of hypoinsulinemic state. The study results provide rationale for large well-designed studies evaluating in-depth clinical relationship of lactate in DKA.